2018
DOI: 10.1371/journal.pone.0197082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a peptide inhibitor for the histone methyltransferase WHSC1

Abstract: WHSC1 is a histone methyltransferase that is responsible for mono- and dimethylation of lysine 36 on histone H3 and has been implicated as a driver in a variety of hematological and solid tumors. Currently, there is a complete lack of validated chemical matter for this important drug discovery target. Herein we report on the first fully validated WHSC1 inhibitor, PTD2, a norleucine-containing peptide derived from the histone H4 sequence. This peptide exhibits micromolar affinity towards WHSC1 in biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…The catalytic segment of NSD3 folds into a compact structure ( Fig. 1h ) as reported previously 5 7 . In the NCP-bound NSD3 C -E1181K/T1232A complex, two kinds of complex particles exhibiting NCP-NSD3 ratios of 1:1 and 1:2 were observed.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The catalytic segment of NSD3 folds into a compact structure ( Fig. 1h ) as reported previously 5 7 . In the NCP-bound NSD3 C -E1181K/T1232A complex, two kinds of complex particles exhibiting NCP-NSD3 ratios of 1:1 and 1:2 were observed.…”
supporting
confidence: 69%
“…Given activating mutations and up-regulation of NSD proteins can both drive tumor progression 1 , 2 , the NSD family of histone lysine methyltransferases are viewed as promising targets for the treatment of several cancer types. Indeed, extensive efforts have been made to identify inhibitors to target the catalytic domain of NSD proteins prior to the resolution of an NCP-bound activating complex structure 5 , 7 , 24 26 . The molecular mechanisms shown in this study should provide valuable information for drug design and development in treating NSD-associated neoplastic diseases.…”
mentioning
confidence: 99%
“…As such, NSD SET domain inhibitors described to date are either very weak 12 , nonselective and without validated binding to the NSD SET domains 13 , or are SAM analogs (e.g. sinefungin) 14 or peptides 15 lacking cellular activity. Therefore, development of drug-like small molecule inhibitors of NSDs with on-target activity in cancer cells remains a major challenge.…”
mentioning
confidence: 99%
“…Structure-activity relationships have been reported for sinefungin analogs, the most potent of which inhibited the SET domains of NSD2 (IC 50 ϭ 1.8 M) and SETD2 (IC 50 ϭ 0.29 M) (41). Also, a peptide inhibitor of NSD2, PTD2 (IC 50 ϭ 3-22 M), has been reported that was derived from the histone H4 sequence (43).…”
mentioning
confidence: 99%